11.1: Invited Paper: Electrofluidic displays: Fast switching, Colorful, low power. (28th November 2018) - Henzen, Alex
Abstract : Electrofluidic and electrowetting displays have been demonstrated since 2004 [1]. They have been subject to extensive investigation, and many of the problems associated with the electrowetting phenomenon were solved. However, new challenges are emerging, in need of a solution. Electrofluidic displays could (and should) play an important role in a growing collection of display technologies, and will add significantly to our interaction with our environment, but is important to understand exactly how to implement and apply this technology. Maybe even more important: How not to apply it. This paper aims to provide an overview of historic achievements and elaborate on more recent progress, while making clear the exciting possibilities of the technology. It will provide a good insight in the current state of the art, and offer guidelines on the factors influencing contrast, brightness and speed.